Tasawuf Aa Gym: Studi Pesan Dakwah KH. Abdullah Gymnastiar - Diana Sari (LP2M UIN Sunan Kalijaga, 2020)
The rise of Sufism shows a new existence in Indonesia. Sufism is not only understood as Sufi teachings and traditional institutions (tarekat). A new passion in Sufism in Indonesia has been seen in cities and among the middle classes. Howell’s research shows the rise of Sufism promoted in two ways (1) ‘Ulamas who come from traditional Islamic education and taught their followers in formal education classes and (2) Television preachers who create their programs and regulate and dramatize it in for the television viewers. New nuances by grounding Sufistic values are also carried out by the KH. Abdullah Gymnastiar who connects his spiritual experience with the world of Sufism, including preaching messages that refer to the teachings of Sufism. This research is a qualitative-field research. The primary source in this study is the da’wah message of KH. Abdullah Gymnastiar. Secondary sources refer to religious studies written in Abdullah Gymnastiar’s social media, book literature, journals/articles, or previous studies. This study uses descriptive analysis to read the da’wah message KH. Abdullah Gymnastiar in his lectures and studies. If placed in the development of the history of Sufism, seen from the character of its religious assembly, Aa Gym is included in the category of contemporary Sufism. However, when viewed from the contents of the principal teachings of moral values, related to the material of da’wah, the message expresed by Aa Gym is the teachings of moral science (ilmu Akhlaq). Broadly speaking, the message of da’wah is not classified as Sufism but religious spirituality which is moral because it contains moral teachings as a reform of morality that synergizes the values of physical and spiritual potential.[The rise of Sufism shows a new existence in Indonesia. Sufism is not only understood as Sufi teachings and traditional institutions (tarekat). A new passion in Sufism in Indonesia has been seen in cities and among the middle classes. Howell’s research shows the rise of Sufism promoted in two ways (1) ‘Ulamas who come from traditional Islamic education and taught their followers in formal education classes and (2) Television preachers who create their programs and regulate and dramatize it in for the television viewers. New nuances by grounding Sufistic values are also carried out by the KH. Abdullah Gymnastiar who connects his spiritual experience with the world of Sufism, including preaching messages that refer to the teachings of Sufism. This research is a qualitative-field research. The primary source in this study is the da’wah message of KH. Abdullah Gymnastiar. Secondary sources refer to religious studies written in Abdullah Gymnastiar’s social media, book literature, journals/articles, or previous studies. This study uses descriptive analysis to read the da’wah message KH. Abdullah Gymnastiar in his lectures and studies. If placed in the development of the history of Sufism, seen from the character of its religious assembly, Aa Gym is included in the category of contemporary Sufism. However, when viewed from the contents of the principal teachings of moral values, related to the material of da’wah, the message expresed by Aa Gym is the teachings of moral science (ilmu Akhlaq). Broadly speaking, the message of da’wah is not classified as Sufism but religious spirituality which is moral because it contains moral teachings as a reform of morality that synergizes the values of physical and spiritual potential.]